(untitled) (Studia austriaca, 2014)
This essay is a reading of Rainer Maria Rilke’s Stunden-Buch, particularly the first book, «Das Buch vom mönchischem Leben» from 1905. Throughout the essay, I develop the question of what prayer means in this cycle of poems, and the relationship of prayer to poetry in general. I argue that Rilke surpasses the usual limitations of language, using poetic techniques that instead of merely indicating objects in the world, have the ability to speak things into being. Furthermore, I argue that Rilke uses language as a protective layer that allows one to transform oneself and face a world that is increasingly hostile to poetic sensibility.